S3D Approach: Incremental Professional Development for Fostering Small-Group Discourse - Sarah Quebec Fuentes (Education Sciences)
The value of discourse in the mathematics classroom is evident across standards, policy documents, and research. The quality of discourse is associated with students’ mathematical understanding and achievement. Productive mathematical discourse includes students providing explanations and critically listening to and evaluating the ideas of others. Such high-level discourse takes time to develop and is impacted by how teachers structure lessons and interact with students (e.g., talk moves). The present case study reports on an incremental professional development, S3D Approach, that guides teachers through a two-phase process to enhance small-group, student-to-student discourse. One middle school mathematics teacher implemented the incremental stages of the S3D Approach with support from a mathematics teacher educator, who conducted weekly observations and debrief meetings. Qualitative analyses revealed that, despite initial challenges, the S3D Approach became integrated into the teacher’s practice, enabling the teacher to identify and build upon incremental improvements in the small-group discourse. Overall, the findings demonstrate how through a reframing of starting points and the definition of success, incremental PD supports sustainable changes in a teacher’s practice and student engagement in productive mathematical discourse.